Secondary battery and electric device

By setting the bonding strengths in different areas in the electrode assembly of the secondary battery, the problem of folding at the end of the diaphragm when falling is solved, the risk of short circuit is reduced, and the safety of use is improved.

CN119650975AActive Publication Date: 2025-03-18NINGDE AMPEREX TECHNOLOGY LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411988656.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-18
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

When the secondary battery falls, the end of the separator of the electrode assembly is easily folded, resulting in short circuit failure between pole sheets of different polarities.

Method used

A secondary battery is designed, and its electrode assembly includes a first electrode sheet, a second electrode sheet and a first diaphragm. The first diaphragm improves its impact resistance by providing adhesive strength in different areas to ensure that it is not easy to fold when falling.

Benefits of technology

By increasing the bonding strength between the first area and the first electrode sheet, the risk of folding at the end of the diaphragm is reduced, the probability of short-circuiting of the secondary battery is reduced, and the safety of use is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650975A_ABST
    Figure CN119650975A_ABST
Patent Text Reader

Abstract

The invention discloses a secondary battery and a power utilization device, the secondary battery comprises an electrode assembly, the electrode assembly comprises a first pole piece, a second pole piece and a first diaphragm, the first pole piece comprises a first tab, and the first tab is arranged on one side of the width direction of the first pole piece; the first diaphragm comprises a first bonding layer and a base film which are stacked; the first bonding layer comprises a first part and a second part which are sequentially arranged in the winding direction, and the first part is far away from the winding center compared with the second part; the first part comprises a first area and a second area, the second part comprises a third area and a fourth area which are sequentially arranged along the width direction of the first diaphragm, and the first area, the third area and the first tab are positioned on the same side of the width direction of the first diaphragm; the bonding strength between the first area and the first pole piece is F1, the bonding strength between the fourth area and the first pole piece is F4, and F1 / F4 is larger than or equal to 1.1. Therefore, the ending part of the first diaphragm on one side of the first tab is not easy to turn over due to falling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage technology, and in particular to a secondary battery and an electrical device. Background Art

[0002] After the electrode assembly of the secondary battery is encapsulated in the shell, there is a certain space between the head of the electrode assembly (the side close to the pole ear) and the shell, causing the electrolyte to accumulate at the head of the electrode assembly. When the secondary battery falls, the end of the diaphragm of the electrode assembly is impacted by the electrolyte, which can easily cause the end of the diaphragm to fold, thereby causing the contact between the pole pieces of different polarities to short-circuit and fail. Summary of the invention

[0003] In view of this, it is necessary to provide a secondary battery that can improve the problem of folding at the end of the head diaphragm of the electrode assembly and reduce the risk of the secondary battery falling and failing.

[0004] A first aspect of an embodiment of the present application provides a secondary battery, comprising an electrode assembly, the electrode assembly comprising a first electrode sheet, a second electrode sheet and a first diaphragm, the first electrode sheet comprising a first electrode ear, the first electrode ear being arranged on one side of the width direction of the first electrode sheet; the first electrode sheet, the first diaphragm and the second electrode sheet are stacked in sequence to form a winding structure; the first diaphragm comprises a first adhesive layer and a base film stacked in a thickness direction of the first diaphragm, the first adhesive layer facing the first electrode sheet; the first adhesive layer comprises a first portion and a second portion connected along the winding direction of the winding structure, the first portion being farther away from the winding center of the winding structure than the second portion; the first portion comprises a first region and a second region sequentially arranged along the width direction of the first diaphragm, the first region and the first electrode ear being located on the same side in the width direction of the first diaphragm; the second portion comprises a third region and a fourth region sequentially arranged along the width direction of the first diaphragm, the third region and the first electrode ear being located on the same side in the width direction of the first diaphragm; the bonding strength between the first region and the first electrode sheet is F1, the bonding strength between the fourth region and the first electrode sheet is F4, and F1 / F4≥1.1.

[0005] In the above-mentioned electrode assembly, when the secondary battery falls, since the first diaphragm corresponding to the first part is farther away from the winding center of the winding structure than the second diaphragm corresponding to the second part, that is, the first diaphragm corresponding to the first part is located at the outer circle of the winding structure, the first diaphragm corresponding to the first part is subjected to a smaller restraining force of the winding structure. Furthermore, the impact force of the electrolyte on the first pole ear side (that is, the head of the electrode assembly) on the first diaphragm corresponding to the first part is greater than the impact force on the first diaphragm corresponding to the second part, and the first diaphragm corresponding to the first area in the first part is located at the head of the electrode assembly where the electrolyte is accumulated, so the impact force of the electrolyte on the first diaphragm position corresponding to the first area is greater. By setting the bonding strength F1 between the first area close to the first pole ear side in the first part and the first pole piece to be relatively large, the firmness of the bonding between the first area and the first pole piece is improved, so that when the electrolyte impacts the first diaphragm corresponding to the first area, the first diaphragm corresponding to the first area is not easily separated from the first pole piece, so that the tail of the first diaphragm located at the head of the electrode assembly is not easy to fold due to falling, reducing the risk of short circuit of the secondary battery caused by direct contact between the first pole piece and the second pole piece. At the same time, since the winding structure corresponding to the fourth area is closer to the winding center than the winding structure corresponding to the first part, the winding binding force of the inner circle of the winding is greater, and the position of the winding structure corresponding to the fourth area is more prone to poor electrolyte infiltration, the bonding strength F4 between the fourth area and the first pole piece should not be too large to avoid aggravating the problem of poor electrolyte infiltration in the winding center of the winding structure. By setting F1 / F4≥1.1, the first area has a relatively high bonding strength compared with the fourth area to achieve the above-mentioned technical effect.

[0006] In one or more of the above embodiments, 1.5≤F1 / F4≤3.5.

[0007] In the above embodiment, the bonding strength F1 between the first region and the first electrode piece and the bonding strength F4 between the fourth region and the first electrode piece should not be too different. If the bonding strength F1 between the first region and the first electrode piece is too large, the probability of poor electrolyte infiltration at the position corresponding to the first region increases. By setting 1.2≤F1 / F4≤3.5, the probability of the first diaphragm corresponding to the first region being folded and the probability of poor electrolyte infiltration at the position corresponding to the first region can be reduced.

[0008] In one or more of the above embodiments, 1.8≤F1 / F4≤2.5.

[0009] In the above embodiment, in order to reduce the probability of folding of the first diaphragm corresponding to the first region and the probability of poor electrolyte infiltration at the position corresponding to the first region, it is further preferred that 1.8≤F1 / F4≤2.5.

[0010] In one or more of the above embodiments, 10 N / m ≤ F1 ≤ 20 N / m; 6 N / m ≤ F4 ≤ 8 N / m.

[0011] In the above embodiment, F1 is in the range of 10N / m to 20N / m, which can take into account both reducing the probability of folding of the first diaphragm corresponding to the first area and reducing the probability of poor electrolyte infiltration problems occurring in the position corresponding to the first area; F4 is in the range of 6N / m to 8N / m, which can take into account both the adhesion force between the first diaphragm corresponding to the fourth area and the first pole piece or the second pole piece and reducing the probability of poor electrolyte infiltration problems occurring in the winding structure corresponding to the fourth area.

[0012] In one or more of the above embodiments, the electrode assembly includes a multi-fold electrode plate area, each folded electrode plate area corresponds to a folded first diaphragm, and the first part is the first bonding layer of the N folded first diaphragms corresponding to the N folded electrode plate areas located at the tail end of the electrode assembly, wherein 1≤N≤3.

[0013] In the above embodiment, the first diaphragm located at the 1st to 3rd fold of the tail end of the electrode assembly is more likely to be folded due to the lack of the constraints of the inner circle electrode sheet and the diaphragm of the winding structure, and is more susceptible to the impact of the electrolyte when the electrode assembly falls, which increases the probability of the first diaphragm at this position being folded. Therefore, the adhesion force of the partial area of ​​the first adhesive layer located at the 1st to 3rd fold position of the tail end of the electrode assembly is increased, so that the probability of the first diaphragm being folded due to falling is reduced. In addition, the more folds of the tail end of the electrode assembly occupied by the first part, the closer the position where the adhesion force increases in the first diaphragm is to the inner circle of the winding structure, which can easily lead to the problem of poor electrolyte infiltration in the inner circle of the winding.

[0014] In one or more of the above embodiments, part of the first pole piece is located at the outermost circle of the winding structure, the first pole piece includes a first surface facing the winding center of the winding structure and a second surface away from the winding center of the winding structure, and the first diaphragm contacts the first surface.

[0015] In the above embodiment, the diaphragm in contact with the outermost pole piece of the winding structure is at the tail end of the electrode assembly. Due to the lack of the constraints of the inner-wound pole piece and the diaphragm, it is more likely to fold. Therefore, the adhesion force of the partial area of ​​the diaphragm in contact with the outermost pole piece of the winding structure is increased, which helps to reduce the probability of the diaphragm in the corresponding area folding.

[0016] In one or more of the above embodiments, the width of the first diaphragm is H, the width of the first region is H1, and 5%≤H1 / H≤50%.

[0017] In the above embodiment, if the width of the first region is too small, the bonding force between the first diaphragm tail located at the head of the electrode assembly and the first pole piece is difficult to meet the requirements, and the improvement of the problem that the first diaphragm corresponding to the first region is prone to folding is small; if the width of the first part is too large, it will affect the wetting effect of the electrolyte on the corresponding position of the first part. When it is within the range of 5%≤H1 / H≤50%, the bonding force requirements of the first region can be met, so that the first diaphragm tail located near the head of the electrode assembly is not easy to fold, and it is not easy to affect the wetting effect of the electrolyte.

[0018] In one or more of the above embodiments, 8%≤H1 / H≤30%.

[0019] In the above embodiment, in order to reduce the probability of folding at the end of the first diaphragm located at the head of the electrode assembly and reduce the influence on the electrolyte infiltration effect, it is further preferred that 8%≤H1 / H≤30%.

[0020] In one or more of the above embodiments, 10%≤H1 / H≤20%.

[0021] In the above embodiment, in order to reduce the probability of folding at the end of the first diaphragm located at the head of the electrode assembly and reduce the influence on the electrolyte infiltration effect, it is further preferred that 10%≤H1 / H≤20%.

[0022] In one or more of the above embodiments, the width of the third region is H3, 0.95≤H3 / H1≤1.05, and the bonding strength between the third region and the first pole piece is F3, 0.95≤F3 / F1≤1.05.

[0023] In the above embodiment, the third region is a region with a width equivalent to that of the first region, and the adhesion force of the third region is set to be equivalent to that of the first region. Then, in the process of preparing the first diaphragm, the third region and the first region can be prepared in one step along the length direction of the first diaphragm, thereby simplifying the preparation process of the first diaphragm and only increasing the adhesion force in the third region, which has little effect on the electrolyte infiltration at the corresponding position of the fourth region, and correspondingly has little effect on the electrolyte infiltration of the inner circle of the winding structure.

[0024] In one or more of the above embodiments, the bonding strength between the second region and the first pole piece is F2, and 0.95≤F2 / F1≤1.05.

[0025] In the above embodiment, the bonding force of the second region is set to be equivalent to the bonding force of the first region, that is, the bonding force of the first part is set to be roughly the same. Then, in the process of preparing the first diaphragm, the first region and the second region can be prepared in one step along the width direction of the first diaphragm, simplifying the preparation process of the first diaphragm and increasing the bonding force of the first part, which is conducive to reducing the increase in the spacing between the first pole piece and the second pole piece at the end of the electrode assembly due to the poor bonding force of the first diaphragm in the later stage of the electrode assembly cycle, the electrolyte bridge breakage, and the purple spots and lithium precipitation problems at the end of the electrode assembly caused by it. In addition, only increasing the bonding force at the first part has little effect on the electrolyte infiltration at the corresponding position of the second part, and correspondingly has little effect on the electrolyte infiltration of the inner circle of the winding structure.

[0026] In one or more of the above embodiments, the first part also includes a fifth region, the fifth region and the first pole piece are located on opposite sides of the first diaphragm in the width direction, and the first region, the second region and the fifth region are arranged in sequence along the width direction of the first diaphragm; the width of the fifth region is H5, 5%≤H5 / H≤50%; the bonding strength between the fifth region and the first pole piece is F5, 0.95≤F5 / F1≤1.05.

[0027] In the above embodiment, in the width direction of the first diaphragm, the electrolyte is easy to accumulate on one side of the first pole ear (i.e., the head side of the electrode assembly in this application) and the opposite side of the first pole ear (this side is defined as the tail side of the electrode assembly in this application), so the first diaphragm located on the head side of the electrode assembly and the tail side of the electrode assembly is more likely to be folded due to the impact of the electrolyte. On the basis of increasing the bonding force of the first area located on the head side of the electrode assembly, further increasing the bonding force of the fifth area located on the tail side of the electrode assembly to be equivalent to the bonding force of the first area can further reduce the probability of the first diaphragm corresponding to the fifth area on the tail side of the electrode assembly being folded.

[0028] In one or more of the above embodiments, the second part also includes a sixth region, the sixth region and the first pole piece are located on opposite sides of the first diaphragm in the width direction, and the third region, the fourth region and the sixth region are arranged in sequence along the width direction of the first diaphragm; the width of the sixth region is H6, 5%≤H6 / H≤50%; the bonding strength between the sixth region and the first pole piece is F6, 0.95≤F6 / F1≤1.05.

[0029] In the above embodiment, on the basis of increasing the adhesive force of the third area located at the head of the electrode assembly, the adhesive force of the sixth area located at the tail side of the electrode assembly is further increased to be equivalent to the adhesive force of the first area, which can further reduce the probability of folding of the first diaphragm corresponding to the sixth area on the tail side of the electrode assembly.

[0030] In one or more of the above embodiments, the first adhesive layer includes a first adhesive, and a coating weight per unit area of ​​the first adhesive in the first region is greater than a coating weight per unit area of ​​the first adhesive in the fourth region.

[0031] In the above embodiment, the greater the coating weight per unit area of ​​the first adhesive, the greater the coating thickness and the greater the bonding force. The bonding force of the first region is improved by increasing the coating thickness of the first adhesive in the first region. Compared with the case where the coating thickness of the first adhesive in the entire first bonding layer is increased, this solution can reduce the overall thickness of the electrode assembly while improving the bonding force between the first region and the first pole piece, which is beneficial to reducing the loss of volume energy density of the secondary battery and reducing the probability of poor electrolyte infiltration at the corresponding position of the fourth region due to excessive bonding force in the fourth region.

[0032] In one or more of the above embodiments, the material of the first binder includes polyvinylidene fluoride; or, the material of the first binder includes polymethyl methacrylate.

[0033] In the above embodiment, the interface gap of the polyvinylidene fluoride material is large, which is conducive to the storage of electrolyte, and can reduce the influence on the electrolyte infiltration effect while improving the bonding strength between the first region and the first electrode plate; compared with polyvinylidene fluoride, the particles of polymethyl methacrylate material are smaller, and under the same bonding force, the thickness of the polymethyl methacrylate coating is thinner, which is conducive to reducing the thickness of the electrode assembly and reducing the loss of volume energy density.

[0034] In one or more of the above embodiments, the particle size of polyvinylidene fluoride is 15 um to 30 um; or, the particle size of polymethyl methacrylate is 0.1 um to 15 um.

[0035] In one or more of the above embodiments, the coating weight per unit area of ​​polyvinylidene fluoride in the first region is G1, and the coating weight per unit area of ​​polyvinylidene fluoride in the fourth region is G2, 4 mg / 5000 mm 2 ≤G1≤10mg / 5000mm 2 , 0.5mg / 5000mm 2 ≤G2<4mg / 5000mm 2 Alternatively, the coating weight per unit area of ​​polymethyl methacrylate in the first region is G3, and the coating weight per unit area of ​​polymethyl methacrylate in the fourth region is G4, 0.7 mg / 5000 mm 2 ≤G3≤10mg / 5000mm 2 , 0.1mg / 5000mm 2 ≤G4<0.7mg / 5000mm 2In the above embodiment, by thickening the polyvinylidene fluoride coating of the first region, the bonding force of the first portion is improved, so that the first region is not easily separated from the first pole piece, thereby reducing the risk of the electrode assembly falling and failing. Alternatively, by thickening the polymethyl methacrylate coating of the first region, the bonding force of the first region is improved, so that the first region is not easily separated from the first pole piece, thereby reducing the risk of the electrode assembly falling and failing.

[0036] In one or more of the above embodiments, the first region includes a first adhesive, and the fourth region includes a second adhesive; the material of the first adhesive includes polymethyl methacrylate, and the material of the second adhesive includes polyvinylidene fluoride.

[0037] In the above embodiment, compared with the polyvinylidene fluoride material, the particles of the polymethyl methacrylate material are smaller and the bonding effect is better. The bonding force of the first region is improved by using a material with greater bonding force in the first region, and under the premise of the same thickness, the bonding force of the polymethyl methacrylate coating is greater, so it is not easy to increase the thickness of the first region, which is conducive to reducing the loss of volume energy density.

[0038] In one or more of the above embodiments, the coating weight per unit area of ​​polymethyl methacrylate in the first region is G5, and the coating weight per unit area of ​​polyvinylidene fluoride in the fourth region is G6, 0.7 mg / 5000 mm 2 ≤G5≤10mg / 5000mm 2 , 0.5mg / 5000mm 2 ≤G6≤4mg / 5000mm 2 .

[0039] In one or more of the above embodiments, the first pole piece is a cathode pole piece.

[0040] In the above-mentioned secondary battery, by increasing the adhesive force of the first region, the end of the first separator is not easily folded due to falling, thereby reducing the risk of contact between the first electrode sheet and the second electrode sheet and improving the safety of the secondary battery.

[0041] A second aspect of the present application provides an electrical device, comprising the secondary battery in the above embodiment.

[0042] In the above-mentioned electrical device, by improving the adhesive force of a partial area of ​​the first separator in the secondary battery, the drop performance and use safety of the secondary battery are improved, thereby improving the use safety of the electrical device. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 is a three-dimensional diagram of a secondary battery in one embodiment of the present application.

[0044] Figure 2 yes Figure 1 A cross-sectional view of the secondary battery along the II-II direction.

[0045] Figure 3 yes Figure 2 Enlarged view of part III.

[0046] Figure 4 is a partial cross-sectional view of an electrode assembly in one embodiment of the present application.

[0047] Figure 5 is a top view of a first bonding layer in one embodiment of the present application.

[0048] Figure 6 is a top view of a first bonding layer in one embodiment of the present application.

[0049] Figure 7 is a schematic diagram of a diaphragm in one embodiment of the present application.

[0050] Figure 8 is a partial cross-sectional view of an electrode assembly in one embodiment of the present application.

[0051] Fig. 9 It is a schematic diagram of an electrical device in one embodiment of the present application.

[0052] Main component symbols 1000, electric device; 100, secondary battery; 10, electrode assembly; 11, first pole piece; 111, first current collector; 112, first active material layer; 113, first electrode tab; 11a, tail end; 11b, first surface; 11c, second surface; 12, second pole piece; 121, second current collector; 122, second active material layer; 123, second electrode tab; 13, separator; 13a, first separator; 131, base film; 132, first adhesive layer; 1321, first portion; 1321a, first region; 1321b, second area; 1321c, fifth area; 1322, second part; 1322a, third area; 1322b, fourth region; 1322c, sixth region; 10a, pole piece region; 10b, main body region; 10c, corner area; 101, straight section; 102, curved section; 133, ceramic layer; 134, second adhesive layer; 13b, second diaphragm; 20, housing; 200, device body; X, first direction; Y, second direction; R, winding direction.

[0053] The following specific implementation methods will further illustrate the present application in conjunction with the above-mentioned drawings. DETAILED DESCRIPTION

[0054] The technical solutions in the embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.

[0055] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0056] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0057] After the electrode assembly of the secondary battery is encapsulated in the shell, there is a certain space between the head of the electrode assembly (the side close to the pole ear) and the shell, causing the electrolyte to accumulate at the head of the electrode assembly. When the secondary battery falls, the end of the diaphragm of the electrode assembly is impacted by the electrolyte, which can easily cause the end of the diaphragm to fold, thereby causing the contact between the pole pieces of different polarities to short-circuit and fail.

[0058] An embodiment of the present application provides a secondary battery, including an electrode assembly, the electrode assembly including a first electrode sheet, a second electrode sheet and a first diaphragm, the first electrode sheet including a first electrode ear, and the first electrode ear is arranged on one side of the width direction of the first electrode sheet; the first electrode sheet, the first diaphragm and the second electrode sheet are stacked in sequence to form a winding structure; the first diaphragm includes a first adhesive layer and a base film stacked in the thickness direction of the first diaphragm, and the first adhesive layer faces the first electrode sheet; the first adhesive layer includes a first part and a second part connected along the winding direction of the winding structure, and the first part is farther away from the winding center of the winding structure than the second part; the first part includes a first region and a second region sequentially arranged along the width direction of the first diaphragm, and the first region and the first electrode ear are located on the same side of the width direction of the first diaphragm; the second part includes a third region and a fourth region sequentially arranged along the width direction of the first diaphragm, and the third region and the first electrode ear are located on the same side of the width direction of the first diaphragm; the bonding strength between the first region and the first electrode sheet is F1, and the bonding strength between the fourth region and the first electrode sheet is F4, and F1 / F4≥1.1.

[0059] In the above-mentioned electrode assembly, when the secondary battery falls, since the first diaphragm corresponding to the first part is farther away from the winding center of the winding structure than the second diaphragm corresponding to the second part, that is, the first diaphragm corresponding to the first part is located at the outer circle of the winding structure, the first diaphragm corresponding to the first part is subjected to a smaller restraining force of the winding structure. Furthermore, the impact force of the electrolyte on the first pole ear side (that is, the head of the electrode assembly) on the first diaphragm corresponding to the first part is greater than the impact force on the first diaphragm corresponding to the second part, and the first diaphragm corresponding to the first area in the first part is located at the head of the electrode assembly where the electrolyte is accumulated, so the impact force of the electrolyte on the first diaphragm position corresponding to the first area is greater. By setting the bonding strength F1 between the first area close to the first pole ear side in the first part and the first pole piece to be relatively large, the firmness of the bonding between the first area and the first pole piece is improved, so that when the electrolyte impacts the first diaphragm corresponding to the first area, the first diaphragm corresponding to the first area is not easily separated from the first pole piece, so that the tail of the first diaphragm located at the head of the electrode assembly is not easy to fold due to falling, reducing the risk of short circuit of the secondary battery caused by direct contact between the first pole piece and the second pole piece. At the same time, since the winding structure corresponding to the fourth area is closer to the winding center than the winding structure corresponding to the first part, the winding binding force of the inner circle of the winding is greater, and the position of the winding structure corresponding to the fourth area is more prone to poor electrolyte infiltration, the bonding strength F4 between the fourth area and the first pole piece should not be too large to avoid aggravating the problem of poor electrolyte infiltration in the winding center of the winding structure. By setting F1 / F4≥1.1, the first area has a relatively high bonding strength compared with the fourth area to achieve the above-mentioned technical effect.

[0060] The embodiments of the present application are further described below in conjunction with the accompanying drawings.

[0061] like Figure 1 and Figure 2 As shown, an embodiment of the present application provides a secondary battery 100, including an electrode assembly 10 and a housing 20, wherein the electrode assembly 10 is accommodated in the housing 20. The electrode assembly 10 includes a first electrode sheet 11, a second electrode sheet 12 and a diaphragm 13, wherein the diaphragm 13 is disposed between the first electrode sheet 11 and the second electrode sheet 12, and the diaphragm 13 is used to isolate the first electrode sheet 11 and the second electrode sheet 12.

[0062] In some embodiments, the housing 20 is a flexible packaging bag, such as an aluminum-plastic film. In other embodiments, the housing 20 is a hard shell, such as a plastic shell, or a metal shell including at least one of a steel alloy, an aluminum alloy, and a copper alloy.

[0063] In some embodiments, an electrolyte (not shown) is injected into the housing 20 , and the electrolyte components include a solvent, an electrolyte salt, and an additive.

[0064] In some embodiments, the electrolyte salt includes at least one of an organic lithium salt or an inorganic lithium salt.

[0065] In some embodiments, the electrolyte salt includes but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium hexafluorocesium oxide (LiCsF6), lithium perchlorate (LiClO4) or lithium trifluoromethanesulfonate (LiCF3SO3).

[0066] In some embodiments, the polarities of the first pole piece 11 and the second pole piece 12 are different. For example, the first pole piece 11 is a cathode pole piece, and the second pole piece 12 is an anode pole piece. For another example, the first pole piece 11 is an anode pole piece, and the second pole piece 12 is a cathode pole piece.

[0067] See also Figure 2 and Figure 3 In some embodiments, the first pole piece 11 includes a first current collector 111 and a first active material layer 112, the first active material layer 112 is disposed on at least one surface of the first current collector 111 along the thickness direction of the first current collector 111, and the diaphragm 13 is disposed between the first active material layer 112 and the second pole piece 12. The thickness direction of the first current collector 111 is the first direction X.

[0068] In some embodiments, along the thickness direction of the first pole piece 11, the first current collector 111 has two oppositely disposed surfaces. The thickness direction of the first pole piece 11 is consistent with the thickness direction of the first current collector 111, and the thickness direction of the first pole piece 11 is the first direction X. A first active material layer 112 is disposed on at least one surface of the first current collector 111, for example, the first active material layer 112 is disposed on two opposite surfaces of the first current collector 111.

[0069] See also Figure 2 and Figure 3 In some embodiments, the second pole piece 12 includes a second current collector 121 and a second active material layer 122. Along the thickness direction of the second pole piece 12, the second current collector 121 has two oppositely disposed surfaces, and the thickness direction of the second pole piece 12 is consistent with the thickness direction of the second current collector 121. The second active material layer 122 is disposed on at least one surface of the second current collector 121, for example, the second active material layer 122 is disposed on both opposite surfaces of the second current collector 121.

[0070] See also Figure 2In some embodiments, for the electrode assembly 10 with a wound structure, the first pole sheet 11 also includes a first pole ear 113, the first pole ear 113 is welded to the first current collector 111, and the first pole ear 113 is arranged on one side of the width direction of the first pole sheet 11, and the width direction of the first pole sheet 11 is the second direction Y.

[0071] In some embodiments, the second pole piece 12 further includes a second pole tab 123 , which is welded to the second current collector 121 and disposed on one side of the second pole piece 12 in the width direction. The width direction of the second pole piece 12 is the second direction Y.

[0072] In some embodiments, the first electrode tab 113 and the second electrode tab 123 are disposed on the same side of the electrode assembly 10 .

[0073] Taking the first pole piece 11 as a cathode pole piece and the second pole piece 12 as an anode pole piece as an example, the first current collector 111 and the second current collector 121 may be metal layers. The first current collector 111 may be a metal layer including at least one of aluminum, nickel, tantalum, titanium, etc., such as aluminum foil. The second current collector 121 may be a metal layer including at least one of copper, nickel, tantalum, titanium, etc., such as copper foil.

[0074] Taking the first pole piece 11 as a cathode pole piece and the second pole piece 12 as an anode pole piece as an example, the polarity of the first active material layer 112 is cathode, and the first active material layer 112 includes cathode active materials, and the cathode active materials may include at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium manganese iron phosphate or lithium manganese oxide, etc. The polarity of the second active material layer 122 is anode, and the second active material layer 122 includes anode active materials, and the anode active materials may include at least one of graphite, hard carbon, soft carbon, silicon, silicon-oxygen materials, silicon-carbon materials, etc.

[0075] See also Figure 3 and Figure 4 In some embodiments, the diaphragm 13 includes a first diaphragm 13a and a second diaphragm 13b. The first pole piece 11, the first diaphragm 13a, the second pole piece 12 and the second diaphragm 13b are stacked in sequence to form a winding structure, and the first pole piece 11 is located at the outermost circle of the winding structure along the winding direction R. The first diaphragm 13a includes a first adhesive layer 132 and a base film 131 stacked along the thickness direction of the first diaphragm 13a, and the first adhesive layer 132 faces the first pole piece 11. The thickness direction of the first diaphragm 13a is the first direction X.

[0076] The first adhesive layer 132 can bond the first diaphragm 13 a to the first pole piece 11 , so that the first diaphragm 13 a is not easily folded or wrinkled relative to the first pole piece 11 .

[0077] In the relevant secondary battery 100, after the wound electrode assembly 10 is packaged, there is a certain space between the head of the electrode assembly 10 and the shell 20. The head of the electrode assembly 10 refers to the side of the electrode assembly 10 provided with the pole ear, which makes it easy for the electrolyte to accumulate at the head of the electrode assembly 10. When the secondary battery 100 falls, the electrolyte accumulated at the head of the electrode assembly 10 is easy to impact the head of the electrode assembly 10, so that the diaphragm 13 at the head of the electrode assembly 10 and near the end of the electrode assembly 10 is easy to separate from the pole piece under the impact force of the electrolyte, thereby causing the diaphragm 13 at the end of the electrode assembly 10 to wrinkle or fold, thereby causing two pole pieces with opposite polarities to directly contact and short-circuit, causing the secondary battery 100 to fail.

[0078] See also Figure 2 and Figure 5 In some embodiments, the first adhesive layer 132 includes a first portion 1321 and a second portion 1322 sequentially disposed along the winding direction R of the winding structure, and the first portion 1321 is farther from the winding center of the winding structure than the second portion 1322. The first portion 1321 includes a first region 1321a and a second region 1321b sequentially disposed along the width direction of the first diaphragm 13a, and the first region 1321a and the first tab 113 are located on the same side of the first diaphragm 13a in the width direction.

[0079] The second portion 1322 includes a third region 1322a and a fourth region 1322b sequentially arranged along the width direction of the first diaphragm 13a, and the third region 1322a and the first pole tab 113 are located on the same side in the width direction of the first diaphragm 13a. The bonding strength between the first region 1321a and the first pole piece 11 is F1, and the bonding strength between the fourth region 1322b and the first pole piece 11 is F4, and F1 / F4≥1.1.

[0080] When the secondary battery 100 falls, since the first diaphragm 13a corresponding to the first part 1321 is farther away from the winding center of the winding structure than the second diaphragm 13b corresponding to the second part 1322, that is, the first diaphragm 13a corresponding to the first part 1321 is located at the outer circle of the winding structure, the first diaphragm 13a corresponding to the first part 1321 is subjected to a smaller restraining force of the winding structure. Furthermore, the impact force of the electrolyte on one side of the first tab 113 (that is, the head of the electrode assembly 10) on the first diaphragm 13a corresponding to the first part 1321 is greater than the impact force on the first diaphragm 13a corresponding to the second part 1322, and the first diaphragm 13a corresponding to the first area 1321a in the first part 1321 is located at the head of the electrode assembly 10 where the electrolyte is accumulated, so the impact force of the electrolyte on the first diaphragm 13a corresponding to the first area 1321a is greater.

[0081] By setting the bonding strength F1 between the first area 1321a near the first pole ear 113 in the first part 1321 and the first pole piece 11 to be relatively large, the bonding firmness between the first area 1321a and the first pole piece 11 is improved, so that when the electrolyte impacts the first diaphragm 13a corresponding to the first area 1321a, the first diaphragm 13a corresponding to the first area 1321a is not easily separated from the first pole piece 11, so that the end of the first diaphragm 13a located at the head of the electrode assembly 10 is not easily folded due to falling, thereby reducing the risk of short circuit of the secondary battery 100 caused by direct contact between the first pole piece 11 and the second pole piece 12. At the same time, since the winding structure corresponding to the fourth area 1322b is closer to the winding center than the winding structure corresponding to the first part 1321, the winding binding force of the inner circle is greater, and the position of the winding structure corresponding to the fourth area 1322b is more prone to poor electrolyte infiltration. Therefore, the bonding strength F4 between the fourth area 1322b and the first pole piece 11 should not be too large, so as not to aggravate the problem of poor electrolyte infiltration in the winding center of the winding structure. By setting F1 / F4≥1.1, the first area 1321a has a relatively high bonding strength compared with the fourth area 1322b, so as to achieve the above-mentioned technical effect.

[0082] In some embodiments, 1.5≤F1 / F4≤3.5. The bonding strength F1 between the first region 1321a and the first pole piece 11 and the bonding strength F4 between the fourth region 1322b and the first pole piece 11 should not differ too much. If the bonding strength F1 between the first region 1321a and the first pole piece 11 is too large, the probability of poor electrolyte infiltration at the position corresponding to the first region 1321a increases. By setting 1.5≤F1 / F4≤3.5, it is possible to reduce the probability of the first diaphragm 13a corresponding to the first region 1321a being folded and the probability of poor electrolyte infiltration at the position corresponding to the first region 1321a being reduced.

[0083] In some embodiments, 1.8≤F1 / F4≤2.5. In order to reduce the probability of the first diaphragm 13a corresponding to the first region 1321a being folded and the probability of poor electrolyte infiltration at the position corresponding to the first region 1321a being reduced, 1.8≤F1 / F4≤2.5 is further preferred.

[0084] In some embodiments, 10 N / m ≤ F1 ≤ 20 N / m. When F1 is within the range of 10 N / m to 20 N / m, the probability of the first diaphragm 13a corresponding to the first region 1321a being folded can be reduced, and the probability of poor electrolyte infiltration at the position corresponding to the first region 1321a can be reduced.

[0085] In some embodiments, 6N / m≤F4≤8N / m. When F4 is within the range of 6N / m to 8N / m, the bonding force between the first diaphragm 13a corresponding to the fourth region 1322b and the first pole piece 11 or the second pole piece 12 can be taken into consideration, and the probability of poor electrolyte infiltration in the winding structure corresponding to the fourth region 1322b can be reduced.

[0086] See also Figure 5 In some embodiments, the width of the first diaphragm 13a is H, the width of the first region 1321a is H1, and 5%≤H1 / H≤50%. If the width of the first region 1321a is too small, the bonding force between the end of the first diaphragm 13a at the head of the electrode assembly 10 and the first electrode sheet 11 is difficult to meet the requirements, and the improvement of the problem that the first diaphragm 13a corresponding to the first region 1321a is prone to folding is small. If the width of the first portion 1321 is too large, it will affect the wetting effect of the electrolyte on the corresponding position of the first region 1321a.

[0087] When it is in the range of 5%≤H1 / H≤50%, the bonding force requirement of the first region 1321a can be met, so that the tail of the first diaphragm 13a located near the head of the electrode assembly 10 is not easy to fold, and is not easy to affect the infiltration effect of the electrolyte.

[0088] In some embodiments, 8%≤H1 / H≤30%. In order to reduce the probability of folding at the end of the first diaphragm 13a at the head of the electrode assembly 10 and reduce the impact on the electrolyte infiltration effect, it is further preferred that 8%≤H1 / H≤30%.

[0089] In some embodiments, it is further preferred that 10%≤H1 / H≤20%.

[0090] See also Figure 5 In some embodiments, the width of the third region 1322a is H3, 0.95≤H3 / H1≤1.05, and the bonding strength between the third region 1322a and the first pole piece 11 is F3, 0.95≤F3 / F1≤1.05. The third region 1322a is a region with a width equivalent to that of the first region 1321a. The bonding strength of the third region 1322a is set to be equivalent to that of the first region 1321a. In the process of preparing the first diaphragm 13a, along the length direction of the first diaphragm 13a, the third region 1322a and the first region 1321a can be prepared in one step, simplifying the preparation process of the first diaphragm 13a, and only increasing the bonding strength at the third region 1322a, which has little effect on the electrolyte infiltration at the corresponding position of the fourth region 1322b, and correspondingly has little effect on the electrolyte infiltration of the inner circle of the winding structure.

[0091] In some embodiments, the bonding strength between the second region 1321b and the first pole piece 11 is F2, 0.95≤F2 / F1≤1.05. The bonding strength of the second region 1321b is set to be equivalent to the bonding strength of the first region 1321a, that is, the bonding strength of the first part 1321 is set to be roughly the same. In the process of preparing the first diaphragm 13a, along the width direction of the first diaphragm 13a, the first region 1321a and the second region 1321b can be prepared in one step, simplifying the preparation process of the first diaphragm 13a, and increasing the bonding strength of the first part 1321, which is conducive to reducing the increase in the spacing between the first pole piece 11 and the second pole piece 12 at the end 11a of the electrode assembly 10 due to the poor bonding strength of the first diaphragm 13a in the later stage of the cycle of the electrode assembly 10, the electrolyte bridging, and the purple spots and lithium precipitation problems at the end 11a of the electrode assembly 10 caused by the poor bonding strength of the first diaphragm 13a. In addition, only increasing the adhesive force at the first portion 1321 has little effect on the electrolyte infiltration at the corresponding position of the second portion 1322, and correspondingly has little effect on the electrolyte infiltration of the inner circle of the winding structure.

[0092] See also Figure 6 In some embodiments, the first portion 1321 further includes a fifth region 1321c, the fifth region 1321c and the first pole tab 113 are located on different sides of the first diaphragm 13a in the width direction, and the first region 1321a, the second region 1321b and the fifth region 1321c are sequentially arranged along the width direction of the first diaphragm 13a. The width of the fifth region 1321c is H5, 5%≤H5 / H≤50%. The bonding strength between the fifth region 1321c and the first pole piece 11 is F5, 0.95≤F5 / F1≤1.05.

[0093] In the width direction of the first diaphragm 13a, the electrolyte is easy to accumulate on one side of the first pole ear 113 (the head side of the electrode assembly 10) and the opposite side of the first pole ear 113 (this side is defined as the tail side of the electrode assembly 10 in this application), so the first diaphragm 13a located on the head side of the electrode assembly 10 and the tail side of the electrode assembly 10 is more likely to be folded due to the impact of the electrolyte. On the basis of increasing the adhesive force of the first area 1321a located on the head side of the electrode assembly 10, the adhesive force of the fifth area 1321c located on the tail side of the electrode assembly 10 is further increased to be equivalent to the adhesive force of the first area 1321a, which can further reduce the probability of the first diaphragm 13a corresponding to the fifth area 1321c on the tail side of the electrode assembly 10 being folded.

[0094] See also Figure 6In some embodiments, the second portion 1322 further includes a sixth region 1322c, the sixth region 1322c and the first pole piece 113 are located on opposite sides of the first diaphragm 13a in the width direction, the third region 1322a, the fourth region 1322b and the sixth region 1322c are sequentially arranged along the width direction of the first diaphragm 13a; the width of the sixth region 1322c is H6, 5%≤H6 / H≤50%; the bonding strength between the sixth region 1322c and the first pole piece 11 is F6, 0.95≤F6 / F1≤1.05.

[0095] On the basis of increasing the adhesion force of the third region 1322a located at the head of the electrode assembly 10, the adhesion force of the sixth region 1322c located at the tail side of the electrode assembly 10 is further increased to be equivalent to the adhesion force of the first region 1321a, which can further reduce the probability of folding of the first diaphragm 13a corresponding to the sixth region 1322c on the tail side of the electrode assembly 10.

[0096] See also Figure 5 or Figure 6 In some embodiments, the first adhesive layer 132 includes a first adhesive, and a coating weight per unit area of ​​the first adhesive in the first region 1321a is greater than a coating weight per unit area of ​​the first adhesive in the fourth region 1322b.

[0097] The greater the coating weight per unit area of ​​the first adhesive, the greater the coating thickness and the greater the bonding force. The bonding force of the first region 1321a is improved by increasing the first adhesive coating thickness of the first region 1321a. Compared with the case where the first adhesive coating thickness in the entire first bonding layer 132 is increased, this solution can reduce the overall thickness of the electrode assembly 10 while improving the bonding force between the first region 1321a and the first pole piece 11, which is beneficial to reducing the loss of the volume energy density of the secondary battery 100 and reducing the probability of poor electrolyte infiltration at the corresponding position of the fourth region 1322b due to excessive bonding force of the fourth region 1322b.

[0098] In some embodiments, the material of the first adhesive includes polyvinylidene fluoride. The polyvinylidene fluoride material has a large interface gap, which is conducive to storing electrolyte and can reduce the impact on electrolyte infiltration effect while improving the bonding strength between the first region 1321a and the first electrode plate 11.

[0099] In some embodiments, the particle size of the polyvinylidene fluoride is 15 um to 30 um.

[0100] In some embodiments, the material of the first binder includes polymethyl methacrylate. Compared with polyvinylidene fluoride, the particles of polymethyl methacrylate material are smaller. Under the same bonding force, the thickness of the polymethyl methacrylate coating is thinner, which is conducive to reducing the thickness of the electrode assembly 10 and reducing the loss of volume energy density of the secondary battery 100.

[0101] In some embodiments, the particle size of polymethyl methacrylate is 0.1 um to 15 um.

[0102] See also Figure 5 or Figure 6 In some embodiments, the coating weight per unit area of ​​the polyvinylidene fluoride in the first region 1321a is G1, and the coating weight per unit area of ​​the polyvinylidene fluoride in the fourth region 1322b is G2, 4 mg / 5000 mm 2 ≤G1≤10mg / 5000mm 2 , 0.5mg / 5000mm 2 ≤G2<4mg / 5000mm 2 .

[0103] By thickening the polyvinylidene fluoride coating of the first region 1321 a , the bonding force of the first portion 1321 is improved, so that the first region 1321 a is not easily separated from the first pole piece 11 , thereby reducing the risk of the electrode assembly 10 falling and failing.

[0104] In some embodiments, the coating weight per unit area of ​​polymethyl methacrylate in the first region 1321a is G3, and the coating weight per unit area of ​​polymethyl methacrylate in the fourth region 1322b is G4, 0.7 mg / 5000 mm 2 ≤G3≤10mg / 5000mm 2 , 0.1mg / 5000mm 2 ≤G4<0.7mg / 5000mm 2 .

[0105] By thickening the polymethyl methacrylate coating of the first region 1321a, the bonding force of the first region 1321a is improved, so that the first region 1321a is not easily separated from the first electrode plate 11, thereby reducing the risk of the electrode assembly 10 falling and failing.

[0106] See also Figure 5 or Figure 6 In some embodiments, the first region 1321a includes a first adhesive, and the fourth region 1322b includes a second adhesive. The material of the first adhesive includes polymethyl methacrylate, and the material of the second adhesive includes polyvinylidene fluoride.

[0107] Compared with polyvinylidene fluoride material, polymethyl methacrylate material has smaller particles and better bonding effect. By using a material with greater bonding force in the first region 1321a, the bonding force of the first region 1321a is improved, and under the premise of the same thickness, the bonding force of the polymethyl methacrylate coating is greater, so it is not easy to increase the thickness of the first region 1321a, which is conducive to reducing the loss of volume energy density of the secondary battery 100.

[0108] In some embodiments, the coating weight per unit area of ​​polymethyl methacrylate in the first region 1321a is G5, and the coating weight per unit area of ​​polyvinylidene fluoride in the fourth region 1322b is G6, 0.7 mg / 5000 mm 2 ≤G5≤10mg / 5000mm 2 , 0.5mg / 5000mm 2 ≤G6≤4mg / 5000mm 2 .

[0109] It can be understood that when the coating weight per unit area of ​​the polymethyl methacrylate material is greater than the coating weight per unit area of ​​polyvinylidene fluoride, the bonding force of the first region 1321a is better than that of the fourth region 1322b, which is beneficial to improve the folding problem of the first diaphragm 13a.

[0110] See also Figure 2 and Figure 7 In some embodiments, the electrode assembly 10 includes a multi-fold electrode sheet area 10a, each folded electrode sheet area 10a corresponds to a folded first diaphragm 13a, and the first part 1321 is a first bonding layer 132 of the N-folded first diaphragms 13a corresponding to the N-folded electrode sheet area 10a located at the tail end 11a of the electrode assembly 10, wherein 1≤N≤3.

[0111] The first diaphragm 13a located at the 1st to 3rd fold of the tail end 11a of the electrode assembly 10 is more likely to be folded due to the lack of the constraints of the inner ring electrode sheet and the diaphragm 13 of the winding structure, and the electrode assembly 10 is more susceptible to the impact of the electrolyte when it falls, which increases the probability of the first diaphragm 13a at this position being folded. Therefore, the adhesion of the partial area of ​​the first adhesive layer 132 located at the 1st to 3rd fold position of the tail end 11a of the electrode assembly 10 is increased, so that the probability of the first diaphragm 13a being folded due to falling is reduced. In addition, the more folds of the tail end 11a of the electrode assembly 10 occupied by the first part 1321, the closer the position where the adhesion increases in the first diaphragm 13a is to the inner ring of the winding structure, which can easily lead to the problem of poor electrolyte infiltration in the inner ring of the winding.

[0112] See also Figure 2 and Figure 3In some embodiments, the first pole piece 11 includes a first surface 11 b facing the winding center of the winding structure and a second surface 11 c away from the winding center of the winding structure, and the first diaphragm 13 a contacts the first surface 11 b .

[0113] The diaphragm 13 in contact with the outermost pole piece of the winding structure is at the tail end 11a of the electrode assembly 10. It is more likely to fold due to the lack of restraint from the inner-wound pole piece and the diaphragm 13. Therefore, increasing the adhesion force of the partial area of ​​the diaphragm 13 in contact with the outermost pole piece of the winding structure is helpful to reduce the probability of folding of the diaphragm 13 in the corresponding area.

[0114] See also Figure 2 and Figure 7 In some embodiments, the electrode assembly 10 includes a main body region 10b and two corner regions 10c, and the straight region is located between the two corner regions 10c. The boundary line P1 between the main body region 10b and the corner region 10c is as shown in FIG. Figure 2 As shown. The electrode assembly 10 includes a straight section 101 and a curved section 102, the straight section 101 and the curved section 102 are connected in sequence, the area where the straight section 101 is located is the main area 10b, and the area where the curved section 102 is located is the corner area 10c. The dividing line P2 between two adjacent folded electrode areas 10a is located in the middle position of the curved section 102 along the winding direction R. It can be understood that a folded electrode area 10a located at the tail end 11a of the electrode assembly 10 is the part between the tail end 11a of the electrode assembly 10 and the dividing line P2.

[0115] In some embodiments, the base film 131 is an insulating film material such as a polyethylene film, a polypropylene film, a polyester film, or a polyimide film.

[0116] See also Figure 8 In some embodiments, the first diaphragm 13a further includes a ceramic layer 133, and the ceramic layer 133 is disposed between the first bonding layer 132 and the base film 131. The provision of the ceramic layer 133 is conducive to the first diaphragm 13a storing more electrolyte for lithium ion transmission, thereby reducing the lithium deposition between the first electrode 11 and the second electrode 12.

[0117] See also Figure 8 In some embodiments, the first diaphragm 13 a includes a second adhesive layer 134 , which is disposed on a side of the base film 131 facing away from the first adhesive layer 132 , and the second adhesive layer 134 faces the second pole piece 12 and is bonded to the second pole piece 12 .

[0118] See also Fig. 9 , an embodiment of the present application further provides an electric device 1000, which includes the secondary battery 100 in any of the above embodiments.

[0119] By improving the adhesive force of the first separator 13 a in the secondary battery 100 , the drop resistance and the use safety of the secondary battery 100 are improved, thereby improving the use safety of the electric device 1000 .

[0120] In some embodiments, the electrical device 1000 may be a mobile phone, a laptop computer, a tablet computer, a drone, an electric tool, an electric toy, a game console, a video recorder, a portable recorder, a radio, or a smart watch, etc., which are not listed one by one here.

[0121] In some embodiments, the power-consuming device 1000 further includes a device body 200, and the secondary battery 100 is installed in the device body 200. Since the power-consuming device 1000 adopts the technical solution of the secondary battery 100 in any of the above embodiments, it has at least the beneficial effects brought by the technical solution of any of the above embodiments of the secondary battery 100, which will not be described one by one here.

[0122] In order to verify the influence of different settings of the separator 13 on the performance of the secondary battery 100, the inventors conducted the following experiments: 1. Peel strength test of the first diaphragm 13a.

[0123] The embodiments and comparative examples of the present application use a high-speed rail tensile machine to test the peel strength of the diaphragm 13 according to GB / T 2792-2014 "Test method for peel strength of adhesive tape". The peel strength is used to characterize the bonding strength of the first part 1321 and the bonding strength of the second part 1322 in Table 1 and Table 2, and the test process is as follows: The secondary battery 100 is discharged to 3.0 V, and then the secondary battery 100 is disassembled, the first separator 13 a is removed as a whole, and the electrolyte on the surface is wiped off with dust-free paper.

[0124] Cut the first part 1321 of the first separator 13a into a strip sample. Paste the 12mm wide end of the green glue with paper, and then compound it with the first separator 13a of the strip sample, roll it 4 times, and cut it to 12mm in width. Use 180° peeling, with the first separator 13a of the strip sample on the upper clamp and the green glue on the lower clamp, at a speed of 20mm / min, take the tensile force data at the position of 10~40mm, calculate the average, and obtain the bonding strength of the first part 1321 of the first separator 13a in a secondary battery 100, in N / m.

[0125] Cut the second part 1322 of the first separator 13a into a strip sample. Paste the 12mm wide end of the green glue with paper, and then compound it with the first separator 13a of the strip sample, roll it 4 times, and cut it to 12mm in width. Use 180° peeling, with the first separator 13a of the strip sample on the upper fixture and the green glue on the lower fixture, at a speed of 20mm / min, take the tensile force data at the position of 10~40mm, calculate the average, and obtain the bonding strength of the second part 1322 of the first separator 13a in a secondary battery 100, in N / m.

[0126] For each group of embodiments and comparative examples, 20 secondary batteries 100 were taken for peel strength test, and the average value was taken to obtain the bonding strength of the first portion 1321 of each group of embodiments and comparative examples.

[0127] 2. Drop test.

[0128] The secondary battery 100 was pre-treated at 25°C, and after standing at room temperature for 60 minutes, the voltage of the lithium-ion battery before the drop test was tested; the secondary battery 100 was placed in a fixture and dropped freely from a position 1.5m above the ground using a drop device in the following order: head-tail-head right corner-tail right corner-head left corner-tail left corner (angle: 45±15°), and repeated 6 rounds. After the drop, it was left at room temperature for 24 hours, and the voltage of the secondary battery 100 was measured and recorded. The appearance of the lithium-ion battery was checked and photographed before and after the test. The drop test pass criteria: no smoke, no leakage, voltage drop <50mV. 20 secondary batteries 100 were tested, and the number of batteries that passed the test was A, and the test pass rate was A / 20.

[0129] 3. Lithium plating rate test.

[0130] Twenty secondary batteries 100 were taken for testing in each group of comparative examples and each group of examples.

[0131] The secondary battery 100 is placed in a test environment at a temperature of 25°C for 30 minutes, and is step-charged to 4.5V according to the following charging steps: ①5C constant current charging to 4.23V, constant voltage charging to 4C; ②4C constant current charging to 4.3V, constant voltage charging to 3C; ③3C constant current charging to 4.4V, constant voltage charging to 2C; ④2C constant current charging to 4.5V, constant voltage charging cut-off current to 0.05C; After standing for 10 minutes, discharge according to the following steps: 0.2C constant current discharge to 3V.

[0132] The above charge and discharge process is one cycle. After repeating 1200 cycles, when the secondary battery 100 is in a fully charged state (the battery design maximum voltage is 4.5V), the secondary battery 100 is disassembled to obtain the negative electrode sheet. The non-lithium deposited area on the surface of the negative electrode sheet is black, and the lithium deposited area is grayish white. If the lithium deposited area on the surface of the negative electrode sheet is greater than or equal to 1mm 2 , it is judged as lithium deposition and the test fails, otherwise it passes. Each group tests 20 pieces, the number of failures is B, and the lithium deposition rate is B / 20.

[0133] Comparative Examples and Examples Preparation of Secondary Battery 100: (1) Preparation of cathode electrode: The cathode active material is lithium cobalt oxide, the cathode conductive agent is acetylene black, and the cathode binder is polyvinylidene fluoride (PVDF, with a weight average molecular weight of 5×10 5 ) are mixed in a mass ratio of 94:3:3, N-methylpyrrolidone (NMP) is added as a solvent, and the cathode slurry is stirred under the action of a vacuum mixer until the solid content is 75wt% and the system is uniform. An aluminum foil with a thickness of 8μm is selected as the cathode current collector, and a foam glue is pasted at a preset position on one surface of the cathode current collector aluminum foil along its thickness direction. The cathode slurry is evenly coated on one surface of the cathode current collector aluminum foil along its thickness direction, and dried at 110°C to obtain a cathode pole piece with a single-sided cathode active material layer (thickness 80μm). After that, the above steps are repeated on the other surface of the aluminum foil along its thickness direction to obtain a cathode pole piece with a double-sided cathode active material layer. Then the previously pasted foam glue is torn off to produce an empty aluminum foil area for welding the cathode pole ear.

[0134] (2) Preparation of anode electrode: The anode active material graphite powder, silicon powder, conductive agent conductive carbon black (Super P), and binder styrene-butadiene rubber (SBR) are mixed in a weight ratio of 67.5:30:1:1.5, and then deionized water is added as a solvent to prepare an anode slurry with a solid content of 50wt%, and stirred evenly. A copper foil with a thickness of 5μm is selected as the anode current collector. The anode slurry is evenly coated on one surface of the anode current collector copper foil along its thickness direction, and dried at 90°C to obtain a single-sided anode pole piece. After the above steps are completed, the single-sided coating of the anode pole piece has been completed. After that, the above steps are repeated on the other surface of the anode pole piece along its thickness direction to obtain an anode pole piece with a double-sided coating of the anode active material layer.

[0135] (3) Preparation of the diaphragm 13: ① Preparation of the first diaphragm 13a: When preparing the first diaphragm 13a of the comparative example and the embodiment shown in Table 1, the first adhesive layer 132 is coated on the base film 131 by gravure coating to form a first part 1321 and a second part 1322 distributed along the width direction of the first diaphragm 13a. The parameters of the first part 1321 and the second part 1322 are shown in Table 1 below.

[0136] ② Preparation of the second separator 13 b: The comparative examples and examples in Table 1 and Table 2 use a polyethylene (PE) porous film with a thickness of 8 μm as the second separator 13 b.

[0137] (4) Preparation of electrolyte: In a dry argon atmosphere, ethylene carbonate, ethyl methyl carbonate and diethyl carbonate were mixed in a mass ratio of 30:50:20 to obtain an organic solution, and then lithium hexafluorophosphate was added to the organic solvent to dissolve and mix evenly to obtain an electrolyte with a lithium salt concentration of 1.15 mol / L.

[0138] (5) Assembly of the secondary battery 100; Ultrasonic welding is used to weld the aluminum pole ear on the empty aluminum foil area preset for welding the cathode pole ear to obtain a cathode pole piece welded with the cathode pole ear; ultrasonic welding is used to weld the nickel pole ear on the empty copper foil area preset for welding the anode pole ear to obtain an anode pole piece welded with the anode pole ear. The above-prepared diaphragm 13, the cathode pole piece welded with the cathode pole ear, the diaphragm 13, and the anode pole piece welded with the anode pole ear are stacked in sequence, and the cathode pole ear and the first part 1321 are located on the same side of the electrode assembly 10, and the electrode assembly 10 is wound. The electrode assembly 10 is placed in the aluminum-plastic film of the packaging bag, and the above-mentioned cathode pole ear and anode pole ear are extended from the top seal edge of the packaging bag. After dehydration at 80°C, the electrolyte is injected and packaged.

[0139] The parameter control and test results of various embodiments and comparative examples are shown in Table 1.

[0140] Table 1 In Table 1, by comparing the experimental data of Comparative Example 1-1 and Example 1-23, it can be seen that by setting F1 / F4≥1.1, the pass rate of the drop test of the secondary battery can be improved. By comparing the experimental data of Example 1-1 to Example 1-10, it can be seen that by increasing the ratio of F1 / F4, the pass rate of the drop test of the secondary battery can be improved. This is because as F1 increases, the bonding between the first region and the first pole piece is more solid, and the first diaphragm corresponding to the first region is not easy to be folded, resulting in safety problems such as short circuit between the first pole piece and the second pole piece. By setting, it can also be seen that as F1 increases, the lithium plating rate of the winding structure corresponding to the first part also increases accordingly. This is because as the bonding strength between the first region and the first pole piece increases, the difficulty of the electrolyte infiltrating the first part increases, resulting in the pole piece position corresponding to the first part being prone to lithium plating due to lack of electrolyte. Among them, when F1 / F4>3.5, the pass rate of the drop test does not increase further, but the lithium plating rate of the winding structure at the position of the first part is further deteriorated due to the further increase of F1. In order to obtain a higher secondary battery drop pass rate while reducing the probability of lithium plating problems in the winding structure corresponding to the first part, 1.5≤F1 / F4≤3.5 is preferred; on this basis, 1.8≤F1 / F4≤2.5 is further preferred.

[0141] By comparing the experimental data of Example 1-1 and Example 1-11 to Example 1-13, it can be seen that the first part is the first bonding layer of the N-folded first diaphragm corresponding to the N-folded pole piece area at the end of the electrode assembly. As N increases, the number of folds occupied by the first part in the electrode assembly increases, and the area of ​​the first area with increased bonding force increases accordingly, so that the pass rate of the drop test of the secondary battery increases with the increase of N; but at the same time, it is also seen that the lithium plating rate of the winding structure at the corresponding position of the first part increases with the increase of N. This is because the inner circle of the winding structure is more prone to poor electrolyte infiltration than the outer circle of the winding structure, resulting in lithium plating. As N increases, the first part is closer to the inner circle of the winding structure, and the bonding strength between the first area in the first part and the first pole piece increases, which aggravates the risk of lack of electrolyte in the winding structure corresponding to the first part, so that the lithium plating rate of the winding structure corresponding to the first part increases. Therefore, in order to take into account both improving the pass rate of the drop test of the secondary battery and reducing the probability of lithium plating in the winding structure corresponding to the first part, the value of N is 1 to 3.

[0142] By comparing the experimental data of Comparative Example 1-1, Example 1-1 and Example 1-14 to Example 1-23, it can be seen that when H1 / H is less than 5%, the drop pass rate of the secondary battery is improved but not significantly compared with Comparative Example 1-1, and as H1 / H increases, the lithium plating rate of the winding structure corresponding to the first part increases. This is because as the width of the first region increases with the increase in adhesion, the difficulty of the electrolyte infiltrating the first part increases, which easily leads to the problem of lithium plating in the winding structure corresponding to the first part due to poor electrolyte infiltration. In order to take into account both improving the drop test pass rate of the secondary battery and reducing the probability of lithium plating in the winding structure corresponding to the first part, 5%≤H1 / H≤50% is set. Preferably, 8%≤H1 / H≤30%. More preferably, 10%≤H1 / H≤20%.

[0143] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present application and are not intended to be limiting of the present application. As long as they are within the spirit and scope of the present application, appropriate changes and modifications to the above embodiments are within the scope of the present application.

Claims

1. A secondary battery, comprising an electrode assembly, characterized in that: The electrode assembly includes a first pole piece, a second pole piece and a first diaphragm, the first pole piece includes a first pole ear, and the first pole ear is arranged on one side of the width direction of the first pole piece; the first pole piece, the first diaphragm and the second pole piece are stacked in sequence to form a winding structure; the first diaphragm includes a first bonding layer and a base film stacked along the thickness direction of the first diaphragm, and the first bonding layer faces the first pole piece; The first adhesive layer includes a first portion and a second portion connected along a winding direction of the winding structure, and compared with the second portion, the first portion is farther away from the winding center of the winding structure; The first part includes a first region and a second region sequentially arranged along the width direction of the first diaphragm, and the first region and the first pole ear are located on the same side in the width direction of the first diaphragm; the second part includes a third region and a fourth region sequentially arranged along the width direction of the first diaphragm, and the third region and the first pole ear are located on the same side in the width direction of the first diaphragm; the bonding strength between the first region and the first pole piece is F1, and the bonding strength between the fourth region and the first pole piece is F4, and F1 / F4≥1.

1.

2. The secondary battery according to claim 1, wherein: 1.5≤F1 / F4≤3.

5.

3. The secondary battery according to claim 2, characterized in that: 1.8≤F1 / F4≤2.

5.

4. The secondary battery according to claim 1, wherein: 10N / m≤F1≤20N / m; 6N / m≤F4≤8N / m.

5. The secondary battery according to claim 1, wherein: The electrode assembly includes a multi-fold electrode area, each fold of the electrode area corresponds to a fold of the first diaphragm, and the first part is a first adhesive layer of the N folds of the first diaphragm corresponding to the N folds of the electrode area located at the tail end of the electrode assembly, wherein 1≤N≤3.

6. The secondary battery according to claim 5, characterized in that: The first pole piece is partially located at the outermost circle of the winding structure. The first pole piece includes a first surface facing the winding center of the winding structure and a second surface away from the winding center of the winding structure. The first diaphragm contacts the first surface.

7. The secondary battery according to claim 1, wherein: The width of the first diaphragm is H, the width of the first region is H1, and 5%≤H1 / H≤50%.

8. The secondary battery according to claim 7, characterized in that 8%≤H1 / H≤30%.

9. The secondary battery according to claim 8, characterized in that 10%≤H1 / H≤20%.

10. The secondary battery according to claim 7, wherein: The width of the third region is H3, 0.95≤H3 / H1≤1.05, and the bonding strength between the third region and the first pole piece is F3, 0.95≤F3 / F1≤1.

05.

11. The secondary battery according to claim 7, characterized in that: The bonding strength between the second region and the first pole piece is F2, 0.95≤F2 / F1≤1.

05.

12. The secondary battery according to claim 7, wherein: The first part also includes a fifth region, and the fifth region and the first pole piece are located on different sides of the first diaphragm in the width direction. The first region, the second region and the fifth region are arranged in sequence along the width direction of the first diaphragm; the width of the fifth region is H5, 5%≤H5 / H≤50%; the bonding strength between the fifth region and the first pole piece is F5, 0.95≤F5 / F1≤1.

05.

13. The secondary battery according to claim 9, wherein: The second part also includes a sixth region, and the sixth region and the first pole piece are located on different sides of the first diaphragm in the width direction. The third region, the fourth region and the sixth region are arranged in sequence along the width direction of the first diaphragm; the width of the sixth region is H6, 5%≤H6 / H≤50%; the bonding strength between the sixth region and the first pole piece is F6, 0.95≤F6 / F1≤1.

05.

14. The secondary battery according to claim 1, wherein: The first adhesive layer includes a first adhesive, and a coating weight per unit area of ​​the first adhesive in the first region is greater than a coating weight per unit area of ​​the first adhesive in the fourth region.

15. The secondary battery according to claim 14, characterized in that: The material of the first binder includes polyvinylidene fluoride; or the material of the first binder includes polymethyl methacrylate.

16. The secondary battery according to claim 15, characterized in that: The particle size of the polyvinylidene fluoride is 15 um to 30 um; or the particle size of the polymethyl methacrylate is 0.1 um to 15 um.

17. The secondary battery according to claim 15, characterized in that: The coating weight per unit area of ​​the polyvinylidene fluoride in the first region is G1, and the coating weight per unit area of ​​the polyvinylidene fluoride in the fourth region is G2, 4 mg / 5000 mm 2 ≤G1≤10mg / 5000mm 2 , 0.5mg / 5000mm 2 ≤G2<4mg / 5000mm 2 ;or, The coating weight per unit area of ​​the polymethyl methacrylate in the first region is G3, and the coating weight per unit area of ​​the polymethyl methacrylate in the fourth region is G4, 0.7 mg / 5000 mm 2 ≤G3≤10mg / 5000mm 2 , 0.1mg / 5000mm 2 ≤G4<0.7mg / 5000mm 2 .

18. The secondary battery according to claim 1, wherein: The first region includes a first adhesive, and the fourth region includes a second adhesive; The material of the first binder includes polymethyl methacrylate, and the material of the second binder includes polyvinylidene fluoride.

19. The secondary battery according to claim 18, wherein: The coating weight per unit area of ​​the polymethyl methacrylate in the first region is G5, and the coating weight per unit area of ​​the polyvinylidene fluoride in the fourth region is G6, 0.7 mg / 5000 mm 2 ≤G5≤10mg / 5000mm 2 , 0.5mg / 5000mm 2 ≤G6≤4mg / 5000mm 2 .

20. The secondary battery according to claim 1, wherein: The first pole piece is a cathode pole piece.

21. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 20.

Citation Information

Patent Citations

  • Secondary battery and electric device thereof

    CN115911513A

  • Electrochemical device and electronic device

    CN117059908A

  • Electrode assembly and battery

    CN117977116A

  • Secondary battery and electric device

    CN118920011A

  • Battery and electronic apparatus using said battery

    WO2022133859A1